Observe, collect, draw! : A visual journal : discover the patterns in your everyday life - Lupi, Giorgia, ....-; Posavec, Stefanie, ....-; McKay, Sara, ....- (New York : Princeton Architectural Press, 2018)
Discover the patterns in your everyday life in a guided visual journal. Harness your skills of observation. Activities teach you how to document the world through colors, lines, shapes, design, and data. Fuel your creativity. Through the lens of data, encourage yourself to notice more closely the unfolding processes of both the world and yourself. Observe, Collect, Draw! functions as a mini-course in information design, as accessible to beginners as it is engaging to seasoned info designers. This journal is for you if you are interested in Self improvement Curious about personal data collection Looking to expand your creative outlets Experimenting with a different way of drawing
Keywords: Drawing; Information design